The role of psychopathy in homicide among juveniles: a review of the research - Ray, James V. (Routledge handbook of homicide studies, 2024)
Psychopathy has shown a strong relationship with homicide particularly among adults. However, little is known about psychopathy and homicide among juveniles. Thus, in this chapter we review the literature examining the association between psychopathy and homicide among juveniles and identify gaps in the literature to guide future research endeavors. To achieve this goal, we first discuss the theoretical link between psychopathy and violent behavior, with a focus on homicide. We then briefly review the research on psychopathy and homicide among adults. Last, we systematically review the research that examines the association between psychopathic traits and homicide in juveniles. We conclude that while psychopathy (particularly the behavior features) and homicide are related; however, there is a considerable amount of research yet to be done in this area to fully understand this relationship.